School‐Based First Aid Training Programs: A Systematic Review. (April 2016) - Reveruzzi, Bianca; Buckley, Lisa; Sheehan, Mary
ABSTRACT: BACKGROUND: This review examines the breadth of first aid training delivered to school students and the components that are age appropriate to adolescents. METHOD: Eligible studies included school‐based first aid interventions targeting students aged between 10 and 18 years. Online databases were searched, for peer‐reviewed publications available as at August 2014. RESULTS: A total of 20 journal articles were relevant to the review. Research supported programs with longer durations (3 hours or more). Most programs taught resuscitation alone and few included content that was context‐specific and relevant to the target group. The training experience of the facilitator did not appear to impact on student outcomes. Incorporating both practical and didactic components was found to be an important factor in delivering material and facilitating the retention of knowledge. Educational resources and facilitator training were found to be common features of effective programs. CONCLUSIONS: The review supports first aid in school curriculum and provides details of key components pertinent to design of school‐based first aid programs. The findings suggest that first aid training may have benefits wider than the uptake and retention of knowledge and skills. There is a need for future research, particularly randomized controlled trials to aid in identifying best practice approaches.